The Phakomatosis (Neurocutaneous Syndromes): Sturge-Weber Syndrome - Ahmad Chitsaz (مجله دانشکده پزشکی اصفهان, 2008)
Neurocutaneous syndromes or phakomatosis are inherited or sporadic conditions that feature lesions of both skin and nervous system. Sturge-weber syndrome (SWS) is characterized by a facial cutaneaous angioma (port-wine nevus) and an associated leptomeningeal and brain angioma; Neurological features of SWS are mental retardation, contra lateral hemiparesis and hemiatrophy and homonymous hemianopia.